Role of Disaggregated Education Expenditure on Economic Growth in Nepal - Adhikari, Gyan Mani; Adhikari, Rajendra; Chhetri, Santosh; Karki, Padam (International Research Journal of MMC, 2025)
This study investigates the nexus between education expenditure and economic growth in Nepal using the Autoregressive Distributed Lag (ARDL) bounds testing approach for the period 1975-2023. Employing time series data, the research disaggregates education spending into recurrent and capital components to analyze their differential impacts on real GDP growth. The empirical findings reveal a significant long-run cointegrating relationship between education expenditure and economic growth. Capital expenditure in education exhibits a positive and statistically significant coefficient (0.262), while recurrent expenditure shows a negative but statistically insignificant relationship (-0.257). The error correction model indicates rapid adjustment to equilibrium with a coefficient of -1.785, suggesting oscillatory convergence. Gross fixed capital formation demonstrates substantial short-run effects on economic growth. These results underscore the importance of prioritizing strategic investments in educational infrastructure while implementing reforms to enhance the efficiency of recurrent expenditure. The study contributes to education finance policy by providing empirical evidence for optimal resource allocation strategies to foster sustainable economic development in Nepal.